ChemInform Abstract: Filling the Gaps in the Challenging Asymmetric Hydroboration of 1, 1‐Disubstituted Alkenes with Simple Phosphite‐Based Phosphinooxazoline Iridium Catalysts. Issue 22 (15th May 2015) - Magre, Marc; Biosca, Maria; Pamies, Oscar; Dieguez, Montserrat
Abstract: Independent of the properties of the aryl substituent, the hydroboration of 1‐alkyl‐1‐aryl styrenes delivers highly enantiopure products.